A STUDY ON STUDENTS’ NEED ANALYSIS ON WEB-BASED ENGLISH LEARNING MATERIALS - Arita Destianingsih; Ari Satria (INOVISH JOURNAL, 2017)
Abstract:The objective of the research was to investigate the needs of students’ analysis in using web-based English learning materials at State Polytechnic of Bengkalis. The research  focused  on  the  students’  professional  needs,  their difficulties of English learning materials while studying, their language skills and tasks, preferred learning styles and teaching methods, and the suggestions for better English learning strategies. This research was used a descriptive analytical approach in order to find the research goals. The data collection used was questionnaire. The research had comprised samples of 50 students randomly from many programs at State Polytechnic of Bengkalis. The participants were both males and females. The research findings revealed that students need to learn English primarily by using web-based English learning materials. Their difficulties in studying could be solved.  Furthermore, the research results indicated that the students were at the beginner level. They wanted to have various learning topics in learning English using website such as the topics related to daily life, science and technology and about teenagers’ life. In learning activities for four skills the students preferred to practice the dialogue in pairs for speaking skill, complete jumble sentences for writing skill, identify key word of the monolog or dialogue for listening, listen to music for vocabulary learning activities and identify grammar error in sentences and write sentences or paragraphs based on the grammar that ever learnt for grammar learning activities.  Keywords: needs analysis, web-based English learning materials, learning                    activities.